Integrating Pancasila Values in Listening-Speaking Materials for Junior High Students - Jamilah, Radhiyatul; Priyana, Joko (Universitas Pendidikan Mandalika, 2025)
This study aims to address the need to promote the integration of Pancasila student profile valuesâ€”specifically independence, critical thinking, and creativityâ€”into listening-speaking supplementary materials for grade VII students at a state junior high school in Kolaka Utara. By understanding the target needs and learning needs, this research seeks to develop listening-speaking supplementary materials that are appropriate for promoting both English language proficiency and Pancasila values. This research employs a research and development (R&D) approach in education, utilizing the well-known ADDIE development model. Data collection methods included qualitative interviews and document analysis, as well as quantitative questionnaires. The needs analysis results indicated that students required materials for learning descriptive text in oral form but faced challenges with word pronunciation, grammar, vocabulary expansion, and understanding spoken information. Consequently, students desired materials that improved their vocabulary and pronunciation with an emphasis on multimedia elements. The listening-speaking supplementary materials integrated the values in implicitly and explicitly. These materials consisted of six units following a genre-based approach and used authentic materials with technology integration. The appropriateness of these materials was demonstrated through positive feedback from students and teachers, who found them engaging, well-aligned with learning objectives, relevant, and sufficient in exercises and tasks. Expert judgment rated the materials with a mean score of 3.9, categorized as â€œvery appropriateâ€ within the range of 3.26 < x â‰¤ 4.00. Furthermore, this research contributed to developing educational resources, and it is expected that students can engage with good value in their future lives.Â